Linear low-density polyethylene gasification over highly active Ni/CeO2-ZrO2 catalyst for enhanced hydrogen generation - Farooq, Abid; Moogi, Surendar; Jang, Seong-Ho; Kannapu, Hari Prasad Reddy; Valizadeh, Soheil; Ahmed, Ashfaq; Lam, Su Shiung; Park, Young-Kwon (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
Steam-gasification of linear low-density polyethylene (LLDPE) waste to hydrogen-rich gas has been studied systematically over nickel (10wt.%) loaded on a variety of supports (Al2O3, CeO2, and CeO2-ZrO2) synthesized using a novel solvent deficient method (SDM). The hydrogen selectivity order of the catalysts was reported as Ni/CeO2-ZrO2>Ni/CeO2>Ni/Al2O3. The highest catalytic H2 selectivity of the Ni/CeO2-ZrO2 catalyst was reported to be ∼76vol.%, and was attributed to the smaller nickel crystals that were finely dispersed on the support, and to formation of Ce1-xZrxO2-δ solid solutions. The Ce1-xZrxO2-δ solid solution in the Ni/CeO2-ZrO2 catalyst was observed to be bi-functional, thus reflecting the acceleration of the water gas shift and the oxidation of carbon to CO and CO2. The better resistance of the Ni/CeO2-ZrO2 catalyst towards coke deposition also indicated its potential for commercial-scale applications for the steam gasification of plastics. Therefore, this research provides an advanced route to recycle LLDPE plastic waste into hydrogen fuel, which presents both economical and environmental benefits.